Constructions of Dense Lattices over Number Fields - Andrade, A.a. [UNESP] (2020)
In this work, we present constructions of algebraic lattices in Euclidean space with optimal center density in dimensions 2;3;4;5;6;8 and 12, which are rotated versions of the lattices Î›n , for n=2,3,4,5,6,8 and K 12. These algebraic lattices are constructed through canonical homomorphism via â„¤-modules of the ring of algebraic integers of a number field.